Influence of B‐Site Disorder on the Properties of Unpoled Bi1/2Na1/2TiO3‐0.06Ba(ZrxTi1‐x)O3 Piezoceramics. Issue 8 (21st April 2016) - Glaum, Julia; Zakhozheva, Marina; Acosta, Matias; Aksel, Elena; Kleebe, Hans‐Joachim; Hoffman, Mark; Schmitt, Ljubomira Ana
Abstract : The influence of B‐site disorder on the dielectric, microstructural, and structural characteristics of unpoled, lead‐free (Bi1/2 Na1/2 )TiO3 ‐0.06Ba(Zr x Ti1‐ x )O3 piezoelectric ceramics with x = 0.02, 0.10, and 0.15 was investigated. The low and medium doping level introduced a stabilization of polar nanoregions reflected in the shift of the dispersive permittivity anomalies to higher temperatures and the development of lamellar rhombohedral domains embedded in the prevalent tetragonal nanodomain matrix. For higher Zr level, the regions of lamellar domains remain, but the dielectric characteristics indicate a reduction in the previous stabilization effect. This behavior is rationalized by a reduction in the correlation length due to the increasing amount of nonpolar sample volume with increasing Zr addition.